A CRITICAL REVIEW OF STANDARDS OF FACILITIES AND INFRASTRUCTURE IN ISLAMIC CONTEXT: THEORY AND PRACTICE - Raudha Meutia; Tria Marvida; Raziska Ibrahimi (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
In the Qur'an, verses are also found that show the importance of facilities and infrastructure or tools in education. In the context of Islamic education, educational tools must contain operational values that are able to deliver to the goals of Islamic education that are full of indigo values. These values are of course based on the existence of the basis or characteristics of Islamic education itself. The approach of this research is qualitative. The type of research used is a literature study. The data collection technique in this study is by documentation. The data analysis technique used is content analysis. The context of the management of facilities and infrastructure from an Islamic perspective is found in the interpretation of the Qur'an Surah An-Nahl (16) verses 68-69 which maps the concept of building the division of labor in arranging infrastructure facilities so that they are effective and on target so that in their implementation they are in accordance with their use value and then strengthened by the hadith of the Prophet PBUH. The inventory of facilities and infrastructure is contained in the interpretation of Surah Al-Baqarah (2) verse 282. Supervision of facilities and infrastructure is contained in the interpretation of surah Al-Mujaadillah (58) verse 7.